Widening Teachers' Reading Repertoires: Moving beyond a Popular Childhood Canon - Cremin, Teresa (Wiley Periodicals LLC, 2025)
To develop a love of reading in the young, teachers need rich repertoires of children's literature and other texts. However, the significance of this subject knowledge is rarely given the attention it deserves in policy, practice, or training contexts. This article, drawing on survey data from England and Finland, underlines these concerns. It reveals that in line with the surveys of practicing teachers, preservice teachers in the study also rely upon a narrow range of high-profile authors, mainly from childhood, and that these very distinctly lack diversity. The authors reflect on the reasons for professional over-reliance on this popular childhood canon and the potentially constraining consequences for child readers. They present key approaches to enable educators to develop diverse, in-depth literary repertoires and argue for the development of Reading Teachers—informed reading role models who effectively deploy responsibility, rigor, and relevance: the three Rs of reading for pleasure.